2014
DOI: 10.15809/irriga.2014v19n1p130
|View full text |Cite
|
Sign up to set email alerts
|

Respostas Morfofisiológicas Da Mamoneira, Em Função Da Salinidade Da Água De Irrigação E Adubação Nitrogenada1

Abstract: O trabalho foi desenvolvido para avaliar as características morfofisiológicas da mamoneira cv. BRS Energia irrigada com águas de diferentes níveis salinos e submetida aos efeitos de doses de nitrogênio, em experimento conduzido em lisímetros de drenagem no campo, pertencente ao Centro de Ciências e Tecnologia Agroalimentar da Universidade Federal de Campina Grande. Os tratamentos foram instalados em blocos ao acaso em esquema fatorial 5 x 4, com três repetições, relativo aos valores de condutividade elétrica d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
2
14
0
2
Order By: Relevance
“…On the other hand, the application of ammonium (NH 4 + ) can contribute to a higher absorption of anions and, in salt-affected soils with high amounts of chlorides, NH 4 + will be absorbed preferentially, causing lower damages to plants. Preliminary results have been observed in experiments with castor bean (SOARES et al, 2013;LIMA et al, 2014) and sunflower (NOBRE et al, 2011;NOBRE et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, the application of ammonium (NH 4 + ) can contribute to a higher absorption of anions and, in salt-affected soils with high amounts of chlorides, NH 4 + will be absorbed preferentially, causing lower damages to plants. Preliminary results have been observed in experiments with castor bean (SOARES et al, 2013;LIMA et al, 2014) and sunflower (NOBRE et al, 2011;NOBRE et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Lima et al (2014), studying the influence of irrigation with saline water with NaCl (ECw from 0.3 to 3.9 dS m -1 ), observed a higher EP (75.47%) in castor bean plants that received 0.3 dS m -1 water and a lower EP (23.16%) in plants under 3.9 dS m -1 water. Among the S 2 , S 3 , S 4 , S 5 , and S 6 treatments (Table 4), the EP of plants irrigated with water containing potassium differed significantly (p < 0.05) from those under irrigation with water containing sodium or calcium.…”
Section: Resultsmentioning
confidence: 99%
“…The volume applied was determined based on plant water demand, estimated through the water balance: applied water volume minus water volume drained in the previous irrigation, plus the leaching fraction of 0.10, according to previous studies (NOBRE et al, 2013;LIMA et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (CAMPOS et al, 2009;SOARES et al, 2012;NOBRE et al, 2013;SANTOS et al, 2013;LIMA et al, 2014aLIMA et al, , 2014b have shown the effects of irrigation water with high salinity on the cultivation of the castor bean cultivar, 'BRS Energia'. However, they are limited to water with different salinity levels; therefore, further studies are necessary, especially on the castor bean 'BRS Gabriela' cultivar, on the effect of nitrogen (N) levels and saline water, to mitigate the negative effects caused by saline stress.…”
Section: Introductionmentioning
confidence: 99%